2001
DOI: 10.1081/dmr-100104400
|View full text |Cite
|
Sign up to set email alerts
|

THE PHARMACOKINETICS OF GLYCYRRHIZIC ACID EVALUATED BY PHYSIOLOGICALLY BASED PHARMACOKINETIC MODELING

Abstract: Glycyrrhizic acid is widely applied as a sweetener in food products and chewing tobacco. In addition, it is of clinical interest for possible treatment of chronic hepatitis C. In some highly exposed subjects, side effects such as hypertension and symptoms associated with electrolyte disturbances have been reported. To analyze the relationship between the pharmacokinetics of glycyrrhizic acid in its toxicity, the kinetics of glycyrrhizic acid and its biologically active metabolite glycyrrhetic acid were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
122
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(135 citation statements)
references
References 70 publications
3
122
2
2
Order By: Relevance
“…It was reported that glycyrrhizic acid (GA) and 18β-glycyrrhetinic acid are the biologically active compounds in Licorice (10). GA, one of the triterpenoid saponin glycoside, was found to protect PC12 cells from 1-methyl-4-phenylpyridinium-induced cytotoxicity (11).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that glycyrrhizic acid (GA) and 18β-glycyrrhetinic acid are the biologically active compounds in Licorice (10). GA, one of the triterpenoid saponin glycoside, was found to protect PC12 cells from 1-methyl-4-phenylpyridinium-induced cytotoxicity (11).…”
Section: Introductionmentioning
confidence: 99%
“…8D. As GL is mainly taken up into the liver, 30 GL-conjugated NPs display a better rate of cell uptake than unconjugated NPs.…”
Section: Cell Uptakementioning
confidence: 99%
“…Glycyrrhizic acid (GL; Figure 1B) is hepatoprotective 28 and has been used to clinically treat patients with chronic active hepatitis. 29 Studies have shown that GL is mainly taken up into the liver 30 and modified liposomes have displayed good livertaxis. 31,32 The surface of GL has been modified based on N-caproyl chitosan and confirmed as a vehicle for hepatocyte targeting.…”
Section: Introductionmentioning
confidence: 99%
“…Активным метаболитом ГК является глицирретовая кислота (ГА), которая по активности значительно превосходит ГК [2,3]. Образование ГА происходит только под действием микрофлоры кишечника [4], доказательством чему является отсутствие ГА в плазме крыс с убитой микрофлорой [5,6]. Несмотря на то, что ГА по биологической активности превосходит ГК, именно последняя входит в состав лекарственных композиций.…”
unclassified